Óptima ubicación y dimensionamiento de D-STATCOM para la compensación de potencia reactiva en redes de distribución considerando la incidencia de armónicos. - Ulloa de Souza, Adrián Gonzalo (2018)
This document proposes an optimization algorithm developed in GAMS environment, by mixed integer non-linear programming, for the optimal placement and sizing of the Static Distribution Compensator (D-STATCOM), in order to perform reactive power compensation to improve the quality and efficiency of the system. The investigation considers the D-STATCOM as an electronic device, so, the study analyze through simple harmonic penetration, the injection of harmonics in the network, to evaluate if the inclusion of the element supposes significant affectation. The model is validated in the distribution systems of 33 and 69-bus of the IEEE; minimizing active power losses and improve the voltage profile, subject to operating restrictions.